2001
DOI: 10.1042/bst0290472
|View full text |Cite
|
Sign up to set email alerts
|

Function of Hrs in endocytic trafficking and signalling

Abstract: The hepatocyte growth factor-regulated tyrosine kinase substrate, Hrs, becomes tyrosine-phosphorylated upon the binding of various growth factors and cytokines to their receptors. This protein is essential for ventral folding morphogenesis, and it shares structural similarity with Vps27p, which is involved in vacuolar protein sorting in yeast. Since Hrs is localized to endosomes and has been implicated in the regulation of signal transduction as well as membrane trafficking, it has been regarded as a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 4 publications
1
44
0
Order By: Relevance
“…Since EGF is known to be associated with its receptor along the degradative endocytic pathway, this could be due to the retention of ubiquitylated EGF-receptor and its ligand within a Hrs-containing sorting machinery capable of ubiquitin binding but incapable of Journal of Cell Science 119 (12) binding clathrin. Deleting the clathrin-box motif, which is only five amino acid residues in the extreme C-terminus of Hrs, does not change the ability of Hrs to bind any of its known interactors other than clathrin, such as STAM, Eps 15 or Tsg101 (Raiborg et al, 2001b;Bache et al, 2003a), and is thus a specific means of studying the effect of clathrin binding without interfering with other interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Since EGF is known to be associated with its receptor along the degradative endocytic pathway, this could be due to the retention of ubiquitylated EGF-receptor and its ligand within a Hrs-containing sorting machinery capable of ubiquitin binding but incapable of Journal of Cell Science 119 (12) binding clathrin. Deleting the clathrin-box motif, which is only five amino acid residues in the extreme C-terminus of Hrs, does not change the ability of Hrs to bind any of its known interactors other than clathrin, such as STAM, Eps 15 or Tsg101 (Raiborg et al, 2001b;Bache et al, 2003a), and is thus a specific means of studying the effect of clathrin binding without interfering with other interactions.…”
Section: Discussionmentioning
confidence: 99%
“…7B,C). Although to a lesser extent, Hrs, a marker of multivesicular bodies (Raiborg et al, 2001) (Fig. 7B,g,k), and Rab7, a marker of late endosomes (Marois et al, 2006) (not shown), also accumulated in rbsn 34 clones.…”
Section: Rbsn-5 Regulates Endocytosis In Drosophilamentioning
confidence: 99%
“…Similar to SARA, the FYVE domain protein-hepatic growth factor-regulated tyrosine kinase substrate (Hrs) has also been linking between the TGF-β/Smad signalling pathway and endosomal membrane trafficking (Raiborg et al, 2001b). Nevertheless, the endosomal targeting of Hrs is via a Rab5-independepent pathway (Raiborg et al, 2001a).…”
Section: Sara-and Rab5-mediated Early Endosome Enlargementmentioning
confidence: 99%